2020
DOI: 10.7554/elife.64919
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-autonomous immune response regulates stress signaling during hypertrophy

Abstract: Postmitotic tissues are incapable of replacing damaged cells through proliferation, but need to rely on buffering mechanisms to prevent tissue disintegration. By constitutively activating the Ras/MAPK-pathway via RasV12-overexpression in the postmitotic salivary glands of Drosophila larvae, we overrode the glands adaptability to growth signals and induced hypertrophy. The accompanied loss of tissue integrity, recognition by cellular immunity and cell death are all buffered by blocking stress signalling through… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(46 citation statements)
references
References 125 publications
(154 reference statements)
6
40
0
Order By: Relevance
“…w 1118 ,Beadex MS1096 -Gal4 (Referred here as Bx : 8860/Bl), w 1118 , w 1118 ;;UAS-Ras V12 (4847/Bl), w 1118 ;;UAS-Drs ( Drs-OE : overexpression [46], w 1118 ; Vkg G00454 /CyO.GFP [48] , UAS-Drs-HA [49], Bx,mCD8::RFP [46] and Sgs3-GFP (5884/Bl) (see also online suppl. Table 1; for all online suppl.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…w 1118 ,Beadex MS1096 -Gal4 (Referred here as Bx : 8860/Bl), w 1118 , w 1118 ;;UAS-Ras V12 (4847/Bl), w 1118 ;;UAS-Drs ( Drs-OE : overexpression [46], w 1118 ; Vkg G00454 /CyO.GFP [48] , UAS-Drs-HA [49], Bx,mCD8::RFP [46] and Sgs3-GFP (5884/Bl) (see also online suppl. Table 1; for all online suppl.…”
Section: Methodsmentioning
confidence: 99%
“…Female virgins were collected for 5 days and crossed to the respective male on day 7. Progeny larvae were grown as described in Ref [46]. Ten to twenty salivary gland pairs were fixed in 4% PFA for 20 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Drosophila AMPs also regulate the gut microbiota downstream of the Imd pathway, a function consistent with their bactericidal activity (Marra et al 2021). However, recent studies have suggested that AMP-like genes may play more subtle roles in other processes like memory formation (Barajas-Azpeleta et al 2018), an erect wing response upon infection (Hanson et al 2021), tumor control (Parvy et al 2019;Araki et al 2019), or regulation of JNK signaling in the salivary gland (Krautz et al 2020). While we confirm a primary importance for Cecropins and other AMPs in the systemic immune response, exploring the functions of AMPs including Cecropins in non-canonical roles is an exciting future direction of research.…”
Section: Discussionmentioning
confidence: 96%